Teratoma Mediastinum - Indra Buana; Sulfia Magfirah (Pusat Riset dan Inovasi Nasional, 2023)
Teratomas are germ cell tumors consisting of somatic tissue derived from two or three germinal layers (ectodermal, endodermal, and mesodermal). Teratomas can be classified as mature teratomas and immature teratomas. Teratomas usually arise in the gonads but can also be extra-gonadal. Extragonadal teratomas can occur in the anterior mediastinum, retroperitoneum, pineal, and anterior suprasellar. The general incidence of teratomas is sacrococcygeal 40%, ovarian 25%, testicular 12%, brain 5%, and others including neck and mediastinum 1%. The etiology of teratoma is unknown, but there is a theory that gonadal and midline teratomas originate from totipotent primordial germ cells. Usually teratomas are found incidentally on thoracic photographs. If symptoms are present, it is generally due to mass effect which may cause coughing, dyspnea or chest pain. Mediastinal teratomas may cause perforation, however this complication is rare but a very serious condition. Large anterior mediastinal teratomas that rupture into the pleural cavity can cause lung infection, pleural effusion and mediastinitis. After complete excision, both mature and immature teratomas have an excellent prognosis.